Management of Bad Loans at Kristina Karawang Multipurpose Cooperative (KSU) - Br Simanjorang, Feby Pebrianti; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
Cooperatives that are synonymous with democratic economic systems are believed to be an alternative solution to socioeconomic problems. The purpose of this study is to determine the factors that cause bad loans, bad loan management, and bad loan settlement at Kristina Karawang KSU Copersi. This study uses a quantitative descriptive method design of data collection through primary data obtained from interviews, observations, and documentation of Mr. Hogen’s KSU. The results of this study show that the level of credit risk is quite healthy based on the NPL ratio. The implementation of the 5C system has a positive impact in minimizing the level of bad loan risk. Bad loan confectionery solutions minimize the opportunity for bad loans to occur which will result in losses in the future. The handling of bad loans has an impact on NPLs where the number of ratios is getting smaller. Judging from the ratio used in the study, it can be classified as quite healthy credit because the ability to supervise credit is increasingly effective.